Implications of Changes in Family Structure and Composition for the Psychological Well-Being of Filipino Women in Middle and Later Years. (February 2017) - Chen, Feinian; Bao, Luoman; Shattuck, Rachel M.; Borja, Judith B.; Gultiano, Socorro
The health implications of multigenerational coresidence for older adults is a well-researched topic in the aging literature. Much less is known of its impact for women in midlife. We used data from the Cebu Longitudinal Health and Nutrition Study (2002, 2005, 2007, and 2012) to study the influence of transitions in multigenerational household composition on depressive symptoms for women in midlife transitioning into old age. Our initial analysis showed little effect when we use the conventional classification of nuclear versus extended family and transition in and out of extended family. When we described shifts in the family environment by compositional changes, that is, change in the presence and absence of particular family members, we found significant association between depressive symptoms and two types of role transitions: the loss of a spouse in the household and the entry and exit of grandchildren in the household.